Assessment of Knowledge, Attitude, and Practice of Obstetricians and Gynecologists Toward Off-Label Medicine Use in Female Reproductive Health Issues - Shakeel, Sadia; Iffat, Wajiha; Qamar, Ambreen; Nesar, Shagufta; Butt, Fareeha; Siddiqui, Sobia Naseem; Rehman, Hina; Rehman, Anees ur (Frontiers in Public Health, 2022)
Background: Off-label medication usage (OLMU) is prevalent in the treatment of various diseases, including female reproductive health issues (FRHIs). However, there is a paucity of literature on the perspective of health professionals on this subject. The purpose of the current study was to assess gynecologists/obstetricians' knowledge, attitude and practice towards OLMU in the treatment of FRHIs. Methods: The current cross-sectional study was conducted in September and October 2021, at five tertiary care hospitals (2 public and 3 private sector), different clinics and maternity homes in a metropolitan city of Karachi, Pakistan. The target population was gynecologists, obstetricians and physicians/residents working in the ob/gyn department in various hospitals and clinical settings of Karachi. Results: The overall response rate was 77.1%. The mean age of the study respondents was 36.1±7.7 years; n=85(55.9%) respondents were working in primary patient care. The majorly reported OLMU by the respondents were clomiphene citrate in unexplained infertility (n=66; 43.4%), metformin to improve cycle regularity in females with polycystic ovary syndrome (PCOS) (n=59; 38.8%) and letrozole to induce ovulation (n=31; 20.4%). The majorly stated categories of OLMU were at a different dose (n=95; 62.5%) and at different indications than approved to treat (n=89; 58.5%). It was reported by the majority of the respondents (n=95; 62.5%) that they do not follow any guidelines or regulations for OLMU in their work setting; however, the response was statistically varied with the working organization (CI 2.14-2.93; p=0.037) and practice area (CI 2.85-4.32; p=0.0001) of respondents. Conclusions: The present study revealed that the respondents were well familiar with the practice of OLMU in the treatment of FRHIs. They expressed their concerns about decreasing such practices by being involved in collective decision-making procedures, and they were inclined to accept initiatives aimed at ensuring drug safety in patients.